2019
DOI: 10.1002/ejsp.2588
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the same coin: The differentiating role of need satisfaction and frustration in passion for screen‐based activities

Abstract: Rooted in Self‐Determination Theory, the present research sought to investigate whether the “bright” and “dark” side of human functioning (need satisfaction and need frustration, respectively) would, as determinants, differentially predict harmonious passion (HP) and obsessive passion (OP) for screen‐based activities such as Facebook use, TV series watching, online gaming, and smartphone gaming. For this purpose, four cross‐sectional studies were carried out (Ntotal = 1,065). Results showed that, across all ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 80 publications
8
64
0
Order By: Relevance
“…Therefore, new research results show that there is substantial overlap (communality) between REA and passion, especially OP (Szabo 2018). Similar findings were reported in non-sports contexts, too, such as in the field of screen-based online behaviors (Orosz et al 2016;Tóth-Király et al 2019b), gambling (MacKillop et al 2006, and work (Birkeland and Buch 2015).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, new research results show that there is substantial overlap (communality) between REA and passion, especially OP (Szabo 2018). Similar findings were reported in non-sports contexts, too, such as in the field of screen-based online behaviors (Orosz et al 2016;Tóth-Király et al 2019b), gambling (MacKillop et al 2006, and work (Birkeland and Buch 2015).…”
supporting
confidence: 54%
“…Empirical studies within the online gaming literature (Brunborg et al 2013;Charlton and Danforth 2007) supported the distinction of high engagement and addiction with the latter including additional components such as withdrawal symptoms that manifest when the individual cannot engage in the given activity. In addition, while addiction is often associated with negative outcomes, this is not necessarily the case for high engagement (e.g., Deleuze et al 2018;Gillet et al 2018;Tóth-Király et al 2019b). For these reasons, OP might be considered as a potential precursor of addiction.…”
Section: Trajectories Of the Risk For Exercise Addiction And Passionmentioning
confidence: 99%
“…These findings, which involved selfreported indicators of maladjustment, were corroborated in studies that made use of objective markers, such as athletes' S-IgA (i.e., immunological protein in saliva; Bartholomew et al, 2011) and elevated blood pressure (Weinstein et al, 2011). A flurry of recent studies has further confirmed the multiple costs associated with need frustration beyond ill-being, as indexed by disordered eating (Verstuyf et al, 2013) as well as rigidly and obsessively pursued behaviors (Tóth-Király et al, 2019). Such findings have been established in different age groups, from adolescents (Talwar and Lee, 2011;Vandenkerckhove, 2019) to adults (Van den Broeck et al, 2016) and seniors living in nursing homes (Ferrand et al, 2019).…”
Section: Need Satisfaction and Need Frustrationmentioning
confidence: 72%
“…Conversely, obsessive passion has been found to be consistently associated with increased negative outcomes (e.g., overuse of media, academic burnout, negative affect) and there is also some evidence of decreased positive outcomes (e.g., vitality). The positive impacts of harmonious passion and negative impacts of obsessive passion have been found across contexts including series watching, facebook use, music, sport and work (Vallerand et al, 2006;Lalande et al, 2017;Tóth-Király et al, 2019). The pattern has been found to be equivalent with respect to videogames, with harmonious passion associated with positive outcomes including skill development, motivation to relax and recreate, post-play energy, life-satisfaction and mental health (Przybylski et al, 2009;Tóth-Király et al, 2019), and obsessive passion related to problematic use of videogames, motivation to procrastinate, and post-play tension (Przybylski et al, 2009;Tóth-Király et al, 2019).…”
Section: Dualistic Model Of Passionmentioning
confidence: 99%